Particle Condensation in Two-Temperature (2T) Arc Plasmas of Various SF6 Replacements - Zhong, Linlin; Baheti, Bayitake; Wu, Qi (Plasma chemistry and plasma processing, 2024)
Fluorinated gases, e.g., CF 3 I, C 3 F 8 , C 4 F 8 , C 4 F 7 N, and C 5 F 10 O, show potential to replace SF 6 in power industry due to their high dielectric strength and low global warming potential . However, particle condensation from arc plasmas of these compounds may reduce dielectric performance. We perform a systematic investigation of particle condensation in two-temperature (2T) arc plasmas of various SF 6 replacements mixed with CO 2 , N 2 , and O 2 , by the Gibbs free energy minimization and entropy maximization methods. The influences of buffer gases, non-equilibrium degree, and gas pressure on particle condensation are discussed in various cases. The results indicate that O 2 is necessary to prevent graphite formation in carbon–fluorine gaseous arcs, and specific mixing ratios of CO 2 and N 2 are required to avoid graphite and iodine crystals in CF 3 I arc plasmas. The relationship between condensation temperature and non-equilibrium degree is complex, with peaks and valleys observed for graphite and iodine crystal condensation temperatures. Moreover, different calculation methods (Gibbs free energy minimization versus entropy maximization) show varying sensitivity of condensation temperatures to pressure changes. All the above findings highlight the importance of considering non-equilibrium effects and multiple condensed species in evaluating arc plasma compositions of SF 6 replacements.